ASSESSMENT OF COMPARATIVE ANALYSIS OF THE COURSE OF NON-ALCOHOLIC FATTY LIVER DISEASE IN MIDDLE-AGED AND ELDERLY PATIENTS WHO SUFFER COVID-19 THROUGH ULTRASOUND ELASTOMETRY (VIA FIBROSCAN) - Zokirov Vohid Zohidovich; Yuldasheva Dilnavoz Xasanovna; Muxammedova Zarifa Ramazzonovna; Nasirova Zarnigor Jasur qizi (Scholar Express Journals, 2021)
The pandemic of the new coronavirus COVID-19 has changed medicine around the world in a major fight against this infection. Patients with chronic liver disease demanded the attention of physicians during the epidemic, as against the background of their exacerbation of the disease increased not only the risk of infection with COVID-19 virus, but also its severity. Diffuse liver disease, especially in the diagnosis of non-alcoholic fatty liver disease, is determined by methods that are safe, non-invasive, and applicable to all patients. Without exception, one such method is the shear wave elastography (fibroscan) examination method. In this study, a comparative study of the course of non-alcoholic fatty liver disease in middle-aged and elderly patients with COVID-19 using a non-invasive instrumental method was performed.
Keywords: COVID-19; non-alcoholic fatty liver disease; hepatic steatosis; steatohepatitis